Multi-Feedstocks Biodiesel Production from Esterification of Calophyllum inophyllum Oil, Castor Oil, Palm Oil and Waste Cooking Oil - Hadiyanto, H; Aini, Apsari Puspita; Widayat, Widayat; Kusmiyati, Kusmiyati; Budiman, Arief; Roesyadi, Achmad (International Journal of Renewable Energy Development, 2020)
Biodiesel can be produced from various vegetable oils and animal fat. Abundant sources of vegetable oil in Indonesia, such as Calophyllum inophyllum, Ricinus communis, palm oil, and waste cooking oil, were used as raw materials. Multi-feedstock biodiesel was used to increase the flexibility operation of biodiesel production. This study was conducted to determine the effect of a combination of vegetable oils on biodiesel characteristics. Degumming and two steps of esterification were applied for high free fatty acid feedstock before trans-esterification in combination with other vegetable oils. Potassium hydroxide was used as a homogenous catalyst and methanol as another raw material. The acid value of C. inophyllum decreased from 54 mg KOH/gr oil to 2.15 mg KOH/gr oil after two steps of esterification. Biodiesel yield from multi-feedstock was 87.926% with a methanol-to-oil molar ratio of 6:1, temperature of 60 ℃, and catalyst of 1%wt. ©2020. CBIORE-IJRED. All rights reserved